A Novel Endophytic Trichoderma longibrachiatum WKA55 With Biologically Active Metabolites for Promoting Germination and Reducing Mycotoxinogenic Fungi of Peanut - Al-Askar, Abdulaziz A.; Rashad, Ehsan M.; Moussa, Zeiad; Ghoneem, Khalid M.; Mostafa, Ashraf A.; Al-Otibi, Fatimah O.; Arishi, Amr Abker; Saber, WesamEldin I. A. (Frontiers in Microbiology, 2022)
Plant residuals comprise the natural habitat of the plant pathogen; therefore, attention is currently focusing on biological-based bioprocessing of biomass residuals into benefit substances. The current study focused on the biodegradation of peanut plant residual (PNR) into citric acid (CA) through a mathematical modeling strategy. Novel endophytic Trichoderma longibrachiatum WKA55 (GenBank accession number: MZ014020.1), having lytic (cellulase, protease, and polygalacturonase) activity, and tricalcium phosphate (TCP) solubilization ability were isolated from peanut seeds and used during the fermentation process. As reported by HPLC, the maximum CA (5505.1 μg/g PNR) was obtained after 9 days in the presence of 15.49 mg TCP, and 15.68 mg glucose. GC–MS analysis showed other bioactive metabolites in the filtrate of the fermented PNR. Practically, the crude product (40%) fully inhibited (100%) the growth and spore germination of three mycotoxinogenic fungi. On peanuts, it improved the seed germination (91%), seedling features, and vigor index (70.45%) with a reduction of abnormal seedlings (9.33%). The current study presents the fundamentals for large-scale production in the industry for the sustainable development of PNR biomass as a natural source of bioactive metabolites, and safe consumption of lignocellulosic-proteinaceous biomass, as well. T. longibrachiatum WKA55 was also introduced as a novel CA producer specified on PNR. Application of the resulting metabolite is encouraged on a large scale.